Hubungan Tingkat Religiusitas terhadap Kecemasan pada Mahasiswa Muslim Angkatan 2011 Universitas Sebelas Maret Surakarta - Larasati, Sekar Ayu; Syamsulhadi, Much; Primadewi, Novi (Nexus Kedokteran Komunitas, 2013)
Background: Anxiety is a part of life; it is a normal phenomenon as long as not disturbing the human activity. The anxiety disorder of the students usually is an anxiety due to a frustration, i.e. everything which is disturbing individualâs ability to achieve their target with a lot of dependants. Religiosity consist of knowledge of religion, religious believes, religious ritual experience, religious experience, religious behavior (morality) and a religiosity social attitudes. With a high religiosity, the life will become more relaxed and peaceful; this is due to the appreciation and behavior that surrender to Allah SWT. Â  Methods: The method that used for the study is an Observational Analytic method with a cross sectional approach.Â  The subject of the study is a Sebelas Maret University of Surakartaâs Moslem student, class of 2011, which involved 150 students as participants.Â  The instruments that used for measurement were L-MMPI Questionnaire, Religiosity Scale and T-MAS Scale which are finally analyzed using Spearman Correlation Test. Â  Results: This study found that there is a negative correlation (inverse relationship), between religiosity level and anxiety, with a weak strengthness (r=-0.29) and statistically significant (p=0.040). Conclusions: Based on the study, there is a negative correlation (inverse relationship), between The Religiosity Level towards Anxiety of Sebelas Maret University of SurakartaâsÂ  Moslem Students Class of 2011. Keywords: Religiosity level, Anxiety, Sebelas Maret University of Surakartaâs Muslim Students